2016
DOI: 10.3390/ijms17060945
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic, Prognostic and Therapeutic Targets of MicroRNAs in Human Gastric Cancer

Abstract: Human gastric cancer (GC) is characterized by a high incidence and mortality rate, largely because it is normally not identified until a relatively advanced stage owing to a lack of early diagnostic biomarkers. Gastroscopy with biopsy is the routine method for screening, and gastrectomy is the major therapeutic strategy for GC. However, in more than 30% of GC surgical patients, cancer has progressed too far for effective medical resection. Thus, useful biomarkers for early screening or detection of GC are esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 239 publications
(237 reference statements)
3
78
0
Order By: Relevance
“…Furthermore, the dysregulation of miRNAs is reported to be involved in the pathogenic processes of GC tumorigenesis by regulating the expression of the miRNA's target genes. It has been revealed that the regulation of miRNAs participating in GC tumorigenesis is associated with cell proliferation and apoptosis-related genes (32). Therefore, numerous studies have suggested that miRNAs, including miR-10b, miR-106a and miR-107, may be used as biomarkers in GC (14,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dysregulation of miRNAs is reported to be involved in the pathogenic processes of GC tumorigenesis by regulating the expression of the miRNA's target genes. It has been revealed that the regulation of miRNAs participating in GC tumorigenesis is associated with cell proliferation and apoptosis-related genes (32). Therefore, numerous studies have suggested that miRNAs, including miR-10b, miR-106a and miR-107, may be used as biomarkers in GC (14,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Evidences have indicated that miRNAs play critical roles in managing many normal biological processes, and abnormal expression of miRNAs is associated with various cancers occurrence, such as gas tric cancer, lung cancer, OS, etc. (12)(13)(14), and miRNAs serve as oncogenes or cancer suppressors during the progression of OS (15,16). For example, Bi et al (17) suggested that miR-100 serves as a cancer inhibitor in OS development via suppressing OS growth by regulating FGFR3 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery in 1993, emerging evidence showed that expression change of miRs is associated with cancer, involving GCs [14,15]. Because they are on intimate terms with tumor genesis, miRs have attracted great attention from researchers to search sensitive and specific biomarkers for early stage cancer.…”
Section: Introductionmentioning
confidence: 99%